1683 Parent Priorities and Preferences at the Outpatient Visit. (October 2012) - Elbadry, M; Deasy, AM; O'Neill, MB
Abstract : Background and Aims: The outpatient care model for children is well established. This study evaluated parent perceptions and understanding of this service in a District General Hospital. Methods: Parents attending a paediatric outpatient clinic were surveyed to discern their health priorities for their child, their understanding of the functioning of the outpatient clinic, the cost accrued by the visit and their views on alternate care delivering systems. Results: Two hundred and forty three surveys were completed by parents. Forty five (18.8%) had children less than 1 year, 91 (38.1%) were between 1 and 5 years, 50 (20.9) were aged 6 to 10 and the remainder were 11 or older. For 202 (84.2%) it was a return visit. Their priorities were. obtaining a diagnosis. achieving health gain for their child. being reassured. being seen by a consultant. being treated with courtesy. having tests performed. Ninety three (44.5%) were aware of how the clinic operated and 112 (49.1%) wished to be seen by a consultant only. To attend the clinic 84 (37.2%) took time off work, 50 (22.6%) required child minding services, 44 (27%) experienced excessive waiting and 198 (88%) accrued parking costs. One hundred and forty three (71.8%) are open to alternate care options other than the traditional outpatient visit with 141 (68.1%) accepting specialist nurse assessment, 122 (55.5%) postal assessment, and 56 (25.2%) telephone assessment by a doctor. Conclusion: The model of outpatient care has changed little in the past decades. While parents understand the process there is active interest in pursuing more family friendly models.